Navigating Insights and Perspectives of Students with Disability to Include in Nepalese Classroom - Khagendra Baraily (MultiTech Publisher, 2024)
Integrated schools with resource classes and special schools provide education for children with disability in Nepal. Government funds and the partial support of national and internal donor partners run these schools. This study intends to seek how children with disability normalize in regular classes after the additional support service in resource class to become a case of inclusion in the education system of Nepal. The study explored the adjustment challenges and identified coping strategies in a regular course. The four students with disability from integrated schools representing children with visual impairment and children with deaf were purposively selected and interviewed through semi-structured interview guidelines in a natural setting. The interview responses were transcribed verbatim and analyzed by extracting themes within a theoretical framework based on post-structuralism and discourse analysis. More than five themes were identified from the discussion of students' reports regarding adjustment challenges in the students' narratives. The study explored significant challenges such as the lack of disabled-friendly physical facilities, domination of traditional methods, presence of an untrained teacher, lack of expanded core curriculum, lack of peer support and poor psychological attachment. The exploration of challenges assists policymakers and well educators set up strategies for effective inclusion in school education and the community. The extreme mitigation of challenges promotes an inclusive atmosphere in regular classrooms.